(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The functionalization of graphene oxide (GO) with polyethylene glycol (PEG) has been widely used in drug delivery systems. This nanocomposite exhibits excellent stability in the presence of high concentrations of salts and proteins and shows to be less toxic than its raw form in vitro and in vivo. However, it must be sterilized before use in the medical field and the gamma irradiation shows a promising option for this purpose. Sterilization by ionizing energy through gamma rays, generated by Cobalt-60 self-disintegration, consists in exposing the materials to short electromagnetic waves. The irradiation process provides substantial advantages when compared to thermal and chemical processes such as more precise control of the process, production of products with superior qualities, lower energy consumption and less environmental pollution. In this work the effect of gamma radiation on the structure of GO and GO functionalized com Amino-PEG (GO-PEG-NH2) irradiated with different doses (15, 25, 35 and 50 kGy) and rate dose 7.31 kGy.h - 1 was evaluated. The analyses were performed by Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy. The results showed that the methods for the synthesis of GO and GO-PEG-NH2 was effective since there was confirmation of the surface oxidation of materials and functionalization with the PEG-NH2 and the sterilization by gamma radiation does not caused any defects on materials.